In vitro inflammatory responses elicited by isolates of Alloiococcus otitidis obtained from children with otitis media with effusion. Issue 3 (April 2014) - Ashhurst-Smith, Christopher; Hall, Sharron T; Burns, Christine J; Stuart, John; Blackwell, C Caroline
Alloiococcus otitidis is usually detected in children with otitis media (OM) by PCR as it is not often detected by routine culture. Our improved method for its isolation obtained A. otitidis from nearly 50% of 78 children with OM with effusion. The role of A. otitidis in pathogenesis of OM is unclear. This study tested two hypothesis: (1) that fresh isolates of A. otitidis would elicit pro-inflammatory cytokines from THP-1 monocytic cells equivalent to those induced by Streptococcus pneumoniae ; (2) priming THP-1 cells with interferon-gamma (IFN-γ) a surrogate for virus infection, would enhance pro-inflammatory responses. Recent clinical isolates of A. otitidis, S. pneumoniae (ATCC 49619) and a blood culture isolate of S. pneumoniae (SP2) were used in the assays. Cytokines were quantified by BioRad bead assay and Luminex 200. IFN-γ priming enhanced cytokine responses. S. pneumoniae ATCC 49619 induced lower responses than SP2 for IL-1β, IL-6, TNF-α. A. otitidis LW 27 elicited higher IL-1β and TNF-α responses than either pneumococcal isolate. Small green colony types of A. otitidis induced higher responses than large white colony types for IL-8 and IL-1β. The hypothesis that A. otitidis elicits cytokines observed in middle ear effusions was supported; the need to use recent clinical isolates in studies of pathogenesis was highlighted.